Atenção primária em diabetes no Sul do Brasil: estrutura, processo e resultado Diabetes mellitus at the primary health care level in Southern Brazil: structure, course of action and outcome - Maria Cecília F Assunção; Iná da Silva dos Santos; Denise P Gigante (Universidade de São Paulo, 2001)
OBJETIVO: Descrever e avaliar a estrutura, o processo e o resultado do cuidado do paciente diabético atendido em nível primário de atenção à saúde em Pelotas, RS. MÉTODOS: O delineamento foi transversal. Foram estudados todos os 32 postos de saúde e 61 médicos que atendem pacientes diabéticos nesses locais. Foi identificada uma amostra de 378 pacientes que tiveram consulta médica nos postos. Os pacientes foram entrevistados em casa, e sua glicemia capilar, pressão arterial e índice de massa corporal foram avaliados e comparados a padrões. Componentes da estrutura e do processo de atendimento foram comparados a padrões recomendados ao manejo de pacientes diabéticos. RESULTADOS: A maioria dos serviços carece de aproximadamente todos os requerimentos mínimos. A aferição da pressão arterial foi o item do exame físico mais relatado na visita inicial. Como plano de tratamento na consulta inicial, cerca de 85% dos médicos relataram prescrever dieta, e 72% exercício físico. Todos os médicos relataram solicitar glicemia de jejum, e 60% hemoglobina glicosilada na monitorização laboratorial dos pacientes. O controle da doença variou de 6% a 11%, conforme os diferentes parâmetros utilizados. CONCLUSÕES: A rede pública de saúde está deficiente, mas existe potencial de melhoria dos três aspectos (estrutura, processo e resultado) através de treinamento em serviço e seguimento de normas-padrão. OBJECTIVE: To describe and evaluate the structure, course of action, and the outcome of diabetic patient care delivered at primary health care level in Pelotas, Southern Brazil. METHODS: Through a cross-sectional study all of 32 health centers in the region were assessed, along with the 61 doctors who were managing diabetic patients. A sample of 378 diabetic patients who attended these health centers was also included. Patients were interviewed at home and their glucose capillary blood level, blood pressure and body mass index were assessed and compared with standard parameters. Course of action and structure components were compared against the basic recommendations for the care of diabetic patients. RESULTS: Most centers didn't meet the basic recommendations. Blood pressure measurement was the most reported action in the physical examination in the first visit. As part of the management plan set in the first visit, almost 85% of the doctors reported to prescribe a special diet and 72% referred recommending physical exercise. For laboratory monitoring, all doctors reported asking for fasting blood glucose and 60% of them reported checking their patients' glycated hemoglobin. The rate of disease control ranged from 6 to 11%, according to the Latin American Diabetes Association and the Ministry of Health parameters, respectively. CONCLUSIONS: Although currently undersupplied, the primary health sector is potentially able to improve in its three components (structure, course of actions and outcome) by training medical doctors and their compliance with established guidelines.